Environmentally-oriented innovative strategies and firm performances in services: Micro-evidence from Italy - Giulio Cainelli; Massimiliano Mazzanti; Roberto Zoboli (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper aims at analysing the role of the environment in innovative strategies based on firm economic performance indicators such as employment, turnover, and labour productivity growth. We exploit a unique dataset of 773 Italian service firms with 20 or more employees comprising 1993-1995 CIS II data on firm innovation strategic motivations and 1995-1998 data on employment, turnover, and labour productivity from the System of the Enterprise Account (SEA). We specify a Gibrat-like empirical model in which the covariates include firm strategies (innovation and environmental), and a set of other explanatory variables and controls. Our econometric findings show a negative link between environmental motivations and growth in employment and turnover and a consequent not significant effect on labour productivity growth. The effect on employment is partly in line with past evidence and may derive from efficiency improvements (dematerialization processes) which also impact on efficiency by reducing workforce number. It is plausible that the net effect derives from the absence of low skilled employment and a creation of high skilled jobs, as a consequence of increased environmental awareness. The effect on turnover shows a negative impact from environmental innovation strategy, implying either a short-medium effect, possibly balanced in the long run by net benefits in terms of higher added value, or a real negative impact, which may be contingent on the observed period, when environmental strategies where not at the heart of strategic management policies. However, productivity-related effects (the core of performance indicators) are not significant. Mainstream hypotheses related to eventual negative impacts are thus not confirmed, although Porter-like effects and virtuous circles between environmentally strategies and performance do not seem to be present.
Keywords: C23; D21; O32; Q55; 330; Services; Firm Environmental Strategies; Firm Growth; CIS Survey; Innovation; Dienstleistungssektor; Umweltmanagement; Innovationsmanagement; Unternehmensentwicklung; Schätzung; Italien